Development of Indonesia Scientific Publications of Physical Education in Reputable International Journals: A Bibliometric Analysis - Hanief, Yulingga Nanda; Kardiyanto, Deddy Whinata; Winarno, Mashuri Eko; Haqiyah, Aridhotul (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2021)
This study aimed to determine trends in scientific publications and map the scope of thematic research in the field of Physical Education, especially for articles published in reputable international journals (Scopus) writen by Indonesian authors. The research process was focused on the following questions: (1) how is the productivity of Physical Education publications developing in Indonesia?; (2) who are the main contributors (author, University, and name of publication) for the published publications?; (3) what are the thematic areas that attract the most attention of academics?; and (4) what topics are emerging in the field of publication?. It’s used the Scopus database as the source of bibliometric analysis data for the research sampling process. The samples were 55 articles found through keyword "physical education" in the "article title" published in international journals indexed by Scopus. This study applied keyword co-occurrence analysis to identify and explore the main thematic areas and topics that appeared in publications. The VOSviewer software was used to support the analysis process and visualize findings. The results of the study show that physical education is a research area that still needs to be developed, referring to the productivity of publications from 2013 to 2020, which the range of publication was still below 15 per year. The collected research results were scattered in the fields of engineering studies (21), social sciences (18), and materials science (14). The main contributor of the publication was Indonesian University of Education (24). The most prolific author was Tedi Supriyadi from the Indonesian University of Education. In the Physical Education publications, six major thematic groups were identified, namely: (1) physical activity of school pupils; (2) sports; (3) Physical Education; (4) health; (5) education; and (6) creativity. This study conveyed to public that the mapping using bibliometric analysis contributes to a better understanding of the development patterns of publications in the field of Physical Education. By finding thematic areas and topics appearing in publications, this study conveys information of important issues for further research and theory development as well as for educational practice or application.